Role of Anti Muscarinic Acetylcholine IgA and anti autoantibodies in whole saliva from Primary Sjögren’s syndrome patients - Borda, Enri Santiago (2016)
Aims: The purpose of this report is to describe saliva IgA antibody against M3 muscarinic acetylcholine receptors (mAChRs) and anti-Ro autoantibodies in patients with primary Sjögren’s syndrome (pSS). In addition we want to clarify if this antibody anti-Ro is or not related to the presence of anti-IgA M3 mAChRs autoantibodies in whole saliva of pSS patients. Methods: Whole saliva samples were collected from healthy volunteers (n=30), patients with pSS anti-Ro positive (n=60) and patients with pSS anti-Ro negative (n=30). Saliva IgA patients and healthy subjects were tested by ELISA recognized the synthetic 25-mer peptide corresponding to the extracellular loop of the human M3 mAChRs. Also, concentration of nitrite/nitrate was determined by ELISA. Results: Optical density values for saliva IgA from pSS anti-Ro positive are significantly higher than those from IgA anti-Ro negative patients and IgA from normal subjects. These molecular interactions between IgA and human M3 mAChR synthetic peptide increased in optical density values compared with IgA from pSS anti-Ro negative and healthy subjects when M3 mAChR synthetic peptide was used as coating antigen. The specificity of this reaction was assessed by the ability of the M3 synthetic peptide (1x10-5 M) to inhibit the action when whole saliva was incubated previously with the M3 synthetic peptide for 40 min at 37ºC and then added together in the microtiter plates. On the other hand, the concentration of nitrate/nitrite in whole saliva was significantly decreased in pSS anti-Ro positive patients in comparison with those from IgA anti-Ro negative patients and healthy subjects. Conclusions: Patients presenting in saliva anti IgA anti-Ro positive are statistically significant in optical density values than those IgA from anti-Ro negative patients and healthy individuals. Also, the hypofunction of the salivary glands is associated with significant decrement of nitrate/nitrites levels in the saliva in pSS-Ro positive without any changes in pSS-Ro negative and healthy subjects.